The Geometric Design of Horizontal Curved on Jalan Drono – Nganom, Wonogiri Using Autocad® Civil 3D - Viranti Fahra Salsabila; Andri Irfan Rifai; Muhammad Isradi (International Journal Labs, 2022)
An efficient network of highway infrastructure is a decisive factor in promoting the socio-economic development of a region. Road construction is intended to connect isolated areas and promote economic growth through good population mobility considering comfort, safety, and smoothness by keeping abreast of transportation technology developments. They were planning the geometric design of the highway through the process of selecting the appropriate geometric aspects as well as design controls that govern the critical elements of the highway design. The current trend of planning for geometric road design is directed at using computer programs to make the results more precise and save time and effort. In this geometric planning, the author plans a geometric horizontal curved road on the Jalan Drono - Nganom, Ngadirojo District, Wonogiri Regency, using AutoCAD Civil 3D®. The creation of this road aims to facilitate the flow of transportation and economic equality of the area with two SCS (Spiral–Circle–Spiral) type bends, a radius of 400 m, a plan speed (Vr) of 80 km/h, a maximum slope of 0.06 and a friction coefficient of 0.14.